PyLiGram – Research Application for LiDAR Data Processing Based on Photogrammetric Methods - Rzonca, Antoni; Twardowski, Mariusz (Geomatics and Environmental Engineering, 2025)
This paper presents the functionality and research possibilities of an application that is based on two concepts: the use of photogrammetric analysis for LiDAR data processing (lidargrammetry), and the assignments of identifiers to cloud points in order to be able to return to the original points after processing without data loss and redundant processing. The research tool has, thus far, been developed for the implementation of two distinct LiDAR data-enhancement processes. The initial approach involves the altimetric transformation of the LiDAR data (a process that is founded on the principles of stereo model deformation theory), and the second process employs lidargrammetry for the purpose of 3D local point-cloud corrections, global changes, or non-rigid transformation. This is achieved by applying blocks of lidargrams and their subsequent matching and adjustments.